A 9-year retrospective evaluation of 102 pressure ulcer reconstructions. (1st September 2020) - Kenneweg, K. A.; Welch, M. C.; Welch, P. J.
Abstract : Objective: Several pressure ulcer (PU) risk factors including paralysis and age greater than 70 have been identified, while others such as nutrition are debated. The object of this study is to identify perioperative risk factors that may predict improved outcomes and reduced complications in primary and recurrent PU reconstructions. Method: A retrospective chart review of patients treated surgically for PUs from 2004 to 2013 at the University of Toledo Medical Center, Toledo, Ohio, US, was completed. Data collected included ulcer and medical history, as well as risk factors, complications and postoperative outcome. Data were statistically analysed for perioperative variances between primary and recurrent ulcers and closure status. Results: A total of 49 patients with 102 reconstructions were reviewed. Spinal cord injured patients accounted for 90% receiving flap coverage of ulcers. Numerous differences between primary and recurrent ulcers were identified, including ulcer location, patient nutritional status, wound infection, postoperative course and recurrence. Multivariate analysis revealed a flap reconstruction prediction model using creatinine, haematocrit, haemoglobin, and prealbumin that is able to successfully predict closure outcome in 83.6% of cases. Conclusion: Many factors play a role in the development, course and treatment of PUs. It is vital to understand the role of patient risk factors in the development of PUs, to direct subsequent management and reconstruction, and to prevent future recurrences.